2020
DOI: 10.7150/thno.45124
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum stress-dependent expression of ERO1L promotes aerobic glycolysis in Pancreatic Cancer

Abstract: Rationale: Endoplasmic reticulum oxidoreductase 1 alpha (ERO1L) is an endoplasmic reticulum (ER) luminal glycoprotein that has a role in the formation of disulfide bonds of secreted proteins and membrane proteins. Emerging data identify ERO1L as a tumor promoter in a wide spectrum of human malignancies. However, its molecular basis of oncogenic activities remains largely unknown. Methods: Pan-cancer analysis was performed to determine the expression profile and prognostic val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 40 publications
(43 reference statements)
2
48
0
Order By: Relevance
“…Treatment with glutathione (GSH) inhibitors results in a significant increase in ROS levels and a transient upregulation in glycolysis in PDAC cells. However, this treatment does not augment ROS-mediated long-term promotion of cell proliferation upon hypoxia-activated ERO1L overexpression, suggesting that high ROS levels may induce an oxidative stress in PDAC cells and ultimately decrease cell viability [ 73 ]. ROS generation is induced in a HIF-1α-independent manner under hypoxic conditions [ 74 ], but increased ROS is responsible for HIF-1α stabilization [ 75 , 76 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with glutathione (GSH) inhibitors results in a significant increase in ROS levels and a transient upregulation in glycolysis in PDAC cells. However, this treatment does not augment ROS-mediated long-term promotion of cell proliferation upon hypoxia-activated ERO1L overexpression, suggesting that high ROS levels may induce an oxidative stress in PDAC cells and ultimately decrease cell viability [ 73 ]. ROS generation is induced in a HIF-1α-independent manner under hypoxic conditions [ 74 ], but increased ROS is responsible for HIF-1α stabilization [ 75 , 76 ].…”
Section: Introductionmentioning
confidence: 99%
“…Highly proliferative cancer cells preferentially metabolize glucose by aerobic glycolysis rather than through the more energetically efficient oxidative phosphorylation, even in the presence of sufficient oxygen, a phenomenon known as the Warburg effect ( 24 , 25 ). Accumulating evidence suggests that the Warburg effect is closely associated with a poor clinical outcome and exerts critical implications on tumor progression ( 26 , 27 ). In this study, we first performed integrated analysis to characterize hypoxia-related lncRNAs in TNBC through leveraging large-scale TNBC molecular profiles from The Cancer Genome Atlas (TCGA).…”
Section: Introductionmentioning
confidence: 99%
“…To confirm the role of ERO1L in pancreatic cancer migration and invasion, we downregulated ERO1L in the indicated pancreatic cells using shRNAs [ 10 ]. Two PDAC cell lines with relatively higher ERO1L expression, Capan-2 and MiaPaca-2 cells, were selected for loss-of-function study.…”
Section: Resultsmentioning
confidence: 99%
“…Two PDAC cell lines with relatively higher ERO1L expression, Capan-2 and MiaPaca-2 cells, were selected for loss-of-function study. Stable expression of two short hairpin RNA (sh-1, sh-2) targeting ERO1L resulted in >80% decrease in ERO1L expression of Capan-2 and MiaPaca-2 cells [ 10 ]. The transwell assay without coated Matrigel suggested that ERO1L knockdown significantly inhibited pancreatic cancer cell migration ( Figure 2(a) ), whereas the transwell assay with coated Matrigel suggested that ERO1L knockdown significantly suppressed pancreatic cancer cell invasion ( Figure 2(b) ).…”
Section: Resultsmentioning
confidence: 99%